2015
DOI: 10.13060/00380288.2015.51.3.180
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Polish Migrant Moral Panic in the UK: Rethinking Employment Insecurities and Moral Regulation

Abstract: This article examines British societal reactions to Polish migrant workers using a framework that combines recent developments of the moral panic concept informed by the sociology of moral regulation and risk governance studies. Given the multi-mediated nature of contemporary moral panics and in contrast to conventional analysis focusing on newspaper coverage this article is based on Polish migrants' self-reported experiences. Moral panic claims-making about Polish workers 'taking British jobs' and 'abusing Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…They concerned the threats stemming from the massive inflow of migrants from this part of the Europe after the accession to the EU. These concerned the expected growth in crime (Mawby & Gisby, 2009) and the weakening position of native British people on a labor market (Fitzgerald & Smoczynski, 2015). These episodes, as the majority of moral panics, were orchestrated and steered by tabloid press.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…They concerned the threats stemming from the massive inflow of migrants from this part of the Europe after the accession to the EU. These concerned the expected growth in crime (Mawby & Gisby, 2009) and the weakening position of native British people on a labor market (Fitzgerald & Smoczynski, 2015). These episodes, as the majority of moral panics, were orchestrated and steered by tabloid press.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Similarly, Bergmann (2018) argues UKIP’s ‘Breaking Point’ (p. 130) poster permeated fear and panic among the citizenry. Importantly, Fitzgerald and Smoczyński (2015) offer more nuance, claiming hostilities ought to be analysed alongside labour market insecurity, competition and the 2008 financial crisis. Relatedly, they assert that society has profoundly changed since the moral panic’s original conceptualisation.…”
Section: Neoliberalism and Brexitmentioning
confidence: 99%
“…However, MacKenzie and Forde (2009) criticised the stereotyping of such attitudes, highlighting how the ‘good’ worker was often associated with minimal terms and conditions, that is high levels of exploitation. Whilst investigating how Poles were obtaining employment in the north east and north west food processing 5 and construction sectors, we identified this phenomenon (Fitzgerald, 2007b). Here we found that when trade unions or inspectorates tried to intervene to alleviate issues of exploitation, employers tended to respond by moving migrant workers to other sites, exchanging them for other groups.…”
Section: The Roots Of the Brexit Vote? The Uk's Response To The Accesmentioning
confidence: 99%